Feasibility study of organic matter and Ammonium removal using loofa sponge as a supporting medium in an aerated submerged fixed-film reactor (ASFFR) - Nabizadeh, Ramin; Naddafi, Kazem; Mesdaghinia, Alireza; Nafez, Amir Hosien (Electronic Journal of Biotechnology, 2008)
Biofilm systems are efficient in the removal of organic matter and ammonium from wastewaters. In this study, loofa sponge, a natural product, was used as a supporting medium in an aerated submerged fixed-film reactor to evaluate its performance in removing organic matter and nitrogen from wastewater. Four pilot runs were performed with chemical oxygen demand (COD) concentrations of 100, 200, 300 and 400 mg l-1 to provide an organic loading rate of 0.6, 1.2, 1.8, and 2.4 kg m-3d-1 respectively. In these pilot runs, the influent ammonium nitrogen concentrations were justified to 5, 10, 15 and 20 mg l-1 as N to provide an influent nitrogen loading of 30, 60, 90 and 120 g m-3.d-1 respectively. Although soluble COD removal efficiency greater than 80 percent was achieved up to a loading rate of 2.4 kg m-3d-1, loofa deformation and clogging after 72 days of application might be considered a serious shortcoming during use in full-scale applications. Nitrogen removal efficiency decreased from 85.6% at an organic loading rate of 0.6 kg m-3d-1 to 56.1% at an organic loading rate of 2.4 kg m-3d-1.